Default mode and task‐positive networks connectivity during the N‐Back task in remitted depressed patients with or without emotional residual symptoms. Issue 7 (8th April 2017) - Delaveau, Pauline; Arruda Sanchez, Tiago; Steffen, Ricardo; Deschet, Karine; Jabourian, Maritza; Perlbarg, Vincent; Gasparetto, Emerson Leandro; Dubal, Stéphanie; Costa e Silva, Jorge; Fossati, Philippe
Abstract: Clinical remission of depression may be associated with emotional residual symptoms. We studied the association of emotional blunting, rumination with neural networks dynamics in remitted depressed patients and cognitive performance during an N‐Back task. Twenty‐six outpatients in remission of depression (Hamilton Depressive rating scale score <7) performed an N‐Back task during fMRI assessment. All patients had been treated by paroxetine for a minimum of 4 months. Two subgroups of patients [Nonemotionally blunted (NEB) = 14 and emotionally blunted (EB) = 12] were determined. To identify functional network maps across participants, the Network Detection using Independent Component Analysis approach was employed. Within and between Task Positive Network (TPN) and Default Mode Network (DMN) connectivity were assessed and related to variability of performance on the N‐Back task and rumination. EB and NEB patients were not different for the level of accurate responses at the N‐Back. However over the entire working memory task, the negative correlation between DMN and TPN was significantly lower in the EB than NEB group and was differently related to cognitive performance and rumination. The stronger the negative correlation between DMN and TPN was, the less variable the reaction time during 3‐Back task in NEB patients. Moreover the greater the negative correlation between DMN and TPN was, the lower the rumination score in EB patients. Emotional blunting may be associated with compromised monitoring of rumination and cognitive functioning in remitted depressed patients through altered cooperation between DMN and TPN. The study suggests clinical remission in depression is associated with biological heterogeneity. Hum Brain Mapp 38:3491–3501, 2017 . ©2017 Wiley Periodicals, Inc.